Habitat Use and Survival of Gray Partridge Pairs in Bavaria, Germany - Wolfgang Kaiser; Ilse Storch; John P. Carroll (National Quail Symposium Proceedings, 2017)
Gray partridge (Perdix perdix) habitat studies have been undertaken in a number of countries but have generally focused on winter and brood rearing. We monitored survival of grey partridge pairs relative to habitat during the breeding season. Our study area was located near Feuchtwangen in north-west Bavaria, Germany. During 1991 to 1994, we used compositional analysis to assess habitat with survival and year as covariates for 38 radio-tagged partridge pairs. Comparing study area habitat to habitats within pair home ranges, we found overall habitat use was non-random with no year effect but a significant effect of survival status. Stubble habitat ranked high for both survival categories, whereas those pairs where the radio-tagged bird died were more associated with meadow habitat. Comparing home ranges to individual radio locations, only surviving partridge used habitat differently from availability. Edge and set aside ranked high whereas meadow ranked low in usage. Our results suggest differences between habitats of partridge which died versus those that survived during breeding season. At the landscape level, association with meadow habitat suggests that it may provide cover but may also support predators. Within home ranges, we see edge and set aside possibly providing more cover diversity, suggesting predation avoidance for those that survived. Our data suggests that late winter and early spring periods, where survival may impact numbers of adults going into the breeding season and ultimately recruitment, are also crucial.
Keywords: agriculture; farming; habitat; pairs; survival